Aulas virtuales y su influencia en el rendimiento académico de los estudiantes de décimo año de la Unidad Educativa San Juan - Sánchez Medina, Cindy Lisseth (2018)
In this final report of the research project they will find classified information, especially relevant and very important on the investigation carried out in the Educational Unit "San Juan", parish San Juan, San Francisco De Puebloviejo, the same one that served to study the problem and to verify if the Virtual Classrooms influence the Academic Performance of the students of this institution that was object of study. The content of the report is the explanation of each of the variables of the subject to be studied, and then determine the objectives to be fulfilled of said research, supported by studies of other authors that were cited for their greater credibility, these studies allowed finding the problem that exists in this institution which will also be detailed, which was simultaneously studied to find a solution through the proposal established in this report, with which teachers and students will benefit, which is the development of a manual on the Virtual classrooms.